How did the COVID-19 Pandemic impact Passenger Choice toward Public Transport? The Case of Jakarta, Indonesia - Lista Lista; Muhammad Isradi; Amar Mufhidin; Andri Irfan Rifai (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
The development of public transport in Jakarta, Indonesia, in the last two decades is quite significant. However, the Corona Virus Disease (COVID-19) pandemic has changed people's travel habits. People have concerns about the spread of the virus on public transport. In order to become the primary choice to return to the New Normal, it is necessary to adjust the conditions of public transport. This paper aims to determine the considerations of passengers in determining the choice of using public transport. The research method used is qualitative by collecting data using a questionnaire and analysis using stated preference. The analysis shows that the passenger restriction and tariff discount significantly affect the probability of using public transport in the new-normal era with an R2 of 0.934. The sensitivity test shows that the stricter the passenger restriction and the discount rate, the higher the probability of using public transport.